THE ROLE OF NOTARIAL DEEDS IN ENSURING LEGAL CERTAINTY FOR FOREIGN INVESTMENT IN BATAM FREE TRADE ZONE: A LEGAL FRAMEWORK ANALYSIS - Maniah; Erniyanti; M. Tartib3 (PT. Radja Intercontinental Publishing, 2026)
The Batam Free Trade Zone (FTZ) has emerged as one of Indonesia's most strategic economic corridors, attracting substantial foreign direct investment due to its geographical proximity to Singapore and Malaysia, as well as favorable fiscal incentives. However, the rapid influx of investment necessitates robust legal mechanisms to ensure transactional certainty and protect the rights of all parties involved. This research examines the pivotal role of notarial deeds in providing legal certainty for foreign investment activities within the Batam FTZ. Employing normative juridical methodology with statutory, conceptual, and comparative approaches, this study analyzes the intersection between notarial law frameworks under Law Number 2 of 2014 concerning Notarial Position (UUJN) and the specific regulatory requirements governing the Batam FTZ under Government Regulation Number 62 of 2019. The findings reveal that notarial deeds serve as indispensable instruments for establishing legal certainty through their authentic evidentiary power (volledig en bindende bewijskracht), which provides conclusive proof of legal transactions. However, several challenges persist, including regulatory fragmentation between national notarial standards and local FTZ requirements, inadequate harmonization of land rights documentation, and procedural complexities in cross-border transactions. This research proposes regulatory recommendations to strengthen the notarial framework within the Batam FTZ, thereby enhancing investor confidence and facilitating sustainable economic development in accordance with Gustav Radbruch's triadic legal values of justice, utility, and certainty.